Cross-sectional evidence on the relation between monetary policy, macroeconomic conditions and low-frequency inflation uncertainty - Christian Conrad; Matthias Hartmann (University of Heidelberg, Department of Economics, 2014)
We examine how the interaction between monetary policy and macroeconomic conditions affects inflation uncertainty in the long-term. The unobservable inflation uncertainty is quantified by means of the slowly evolving long-term variance component of inflation in the framework of the Spline-GARCH model (Engle and Rangel, 2008). For a cross-section of 13 developed economies, we find that long-term inflation uncertainty is high if central bank governors are perceived as less inflation-averse and if the conduct of monetary policy is ad-hoc rather than rule-based.
urn:nbn:de:bsz:16-heidok-175344
Keywords: 330; Inflation uncertainty; Central banking; Spline-GARCH